Analisis User Experience Pada Game CS:GO dengan Menggunakan Metode Cognitive Walkthrough dan Metode Heuristic Evaluation - Gagas Pandusarani; Adam Hendra Brata; Eriq Muh. Adams Jonemoro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Counter Strike : Global Offensive is a game First-Person Shooter and is the best game First-Person Shooter according to PC Gamesn and Steam. However, behind all that what can make the game into a famous and successful on market. There is one science that can determine that is, User Experience. User Experience is a very important part in making games. Inside user experience there Interface, Interface is a science that learn the view. Then, to know the game view Counter Strike : Global Offensive is good or not, then analyzed with Cognitive Walkthrough and Heuristic Evaluation method. Cognitive Walkthrough and Heuristic Evaluation is a method that have a lot of similarities and only have one different. Cognitive Walkthrough respondents by beginners, Heuristic Evaluation respondents by experts. The Analysis aims to discover the deficiency of game view, then if any deficiency it will be repaired. The result of the analysis is good, only have one deficiency from testing by experts and can be concluded this game to be the best game because this game have good User Experience.